Employee training in small and medium-sized enterprises in Mongolia (Proceedings of the Mongolian Academy of Sciences, 2019)
In many developed and developing countries, small and medium-sized enterprises (SMEs) play a significantrole in their development. All researches show that globally, SMEs account for more than 90 percent of all business activities and earlier studies have established that SMEs have a critical role in contributing to a country’s economic growth[2] such as reducing poverty and unemployment,and creating employment opportunities. In addition, they contribute to reducing inequitable income distribution, enhancing competitiveness of enterprises, as well as promoting social stability. Therefore, the development of SMEs represents theprimary goal of every modern economy. There are many factors that influence the development of SMEs andone of the most important among them is the human resource management practice, especially employees’ training. Therefore, the main aim of our study is to examine the level of awareness of the training and development (T&D) policy among owners or managers of SMEs, their attitude and organisational support towards training and to analyse the training-related problems encountered by SMEs within the context of Mongolia.